KNOWLEDGE LEVEL OF RURAL PEOPLE ON GRAM SABHA OF DANTIWADA TALUKA OF GUJARAT - SIMPLE JAIN (The Journal of Research ANGRAU, 2016)
Gram Sabha is a constitutional body of all the adult members of a village, irrespective of their caste, class, gender and political leanings and affiliations and represents their needs and aspirations. It establishes the supremacy of the people at the grassroot level of democracy. However, this constitutional body is not functioning properly due to lack of knowledge amongst the members and poor participation in the Gram Sabha. Therefore, the present study was undertaken to assess the knowledge level of rural people about the Gram Sabha. The present study was conducted in three blocks of Dantiwada taluka, district Banaskantha, Gujarat. One village from each block was selected randomly. A sample of 20 women and 20 men were randomly selected from each village. Thus, the total sample of the study was 120 respondents which included 60 women and 60 men. Findings of the study showed that 44.2 per cent respondents had excellent knowledge and 32.5 per cent respondents had less knowledge about Gram Sabha. Majority of the respondents had good knowledge on Gram Sabha whereas men had comparatively more knowledge (0.98) than women (0.17).